The impact of on accessible tourism: the evidence based on a systematic literature review - Teixeira, Pedro (2022)
There is a clear need to address the technological effects of providing conditions for accessibility in tourism. Accessible tourism is becoming very important, and technology may be the tool which will surpass barriers to accessibility in tourism. New information technologies focus not just on the divulgation of information, but also on making sure everything is connected, which in the case of accessible tourism has significant value. Therefore, this chapter aims to share the results of a systematic literature review conducted on the topic of the impact of ICTs on accessible tourism. The research will be done via analysis of a range of bibliometric indicators present in the main academic and research databases. This approach will allow the characterization of the main technologies in the service of accessible tourism and an understanding of how they can enhance the quality of tourism experiences for people with disabilities.